Experience of a year of adult hospital dermatology consultations. (10th November 2014) - Storan, Eoin R.; McEvoy, Marian T.; Wetter, David A.; el‐Azhary, Rokea A.; Camilleri, Michael J.; Bridges, Alina G.; Davis, Mark D. P.
Abstract Background Dermatology consultations are frequently requested by inpatient hospital services. As inpatient dermatology services in the USA decline, dermatology hospital consultations are becoming increasingly important. Objectives We aim to describe the spectrum of skin diseases encountered and the health care subspecialties requesting dermatology hospital consultations. Methods We performed a retrospective chart review of adult patient (age: ≥18 years) dermatology hospital consultations from January 1 to December 31, 2010. We examined patient demographic characteristics, consultation requesting services, and consultation diagnoses. Results Among dermatology services, 614 patients had 674 separate inpatient dermatology consultations during 2010. Of these patients, 55.9% were male (mean age: 59 years). In total, 205 consultations (30.4%) were requested by the internal medicine subspecialty, 137 (20.3%) by the hematology and oncology subspecialty, and 93 (13.8%) by the surgical subspecialty. The most common conditions seen by the hospital dermatology consulting service were skin infections (n = 125, 18.5%), dermatitis (n = 120, 17.8%), drug eruptions (n = 87, 12.9%), chronic wounds and ulcers (n = 55, 8.1%), cutaneous neoplasms (n = 39, 5.8%), graft‐versus‐host disease (n = 37, 5.5%), ecchymosis, purpura simplex or petechia (n = 26, 3.8%), intertrigo (n = 21, 3.1%), and urticaria (n = 20, 3.0%). Conclusions The majority of consultations conducted by the dermatology hospital consulting service were for the management of common skin diseases, such as cutaneous infections, dermatitis, and drug eruptions. Most consultations were requested by the departments of internal medicine, hematology and oncology, and surgical services.